Reassessment of the generic features of starch gelatinization: An advanced SAXS study on maize and potato starch. (December 2022) - Goderis, B.; Dries, D.M.; Nivelle, M.A.; Delcour, J.A.
Abstract: The gelatinization of maize and potato starch granules in excess water [10% starch (w/w)] while heating at 4 °C/min was monitored by time-resolved polarized optical microscopy (POM), synchrotron small-angle X-ray scattering (SAXS), wide-angle X-ray diffraction (WAXD) and differential scanning calorimetry (DSC) measurements. POM confirms that gelatinization is the result of a non-synchronous fast gelatinization of the individual granules over a rather wide temperature range. The WAXD based crystallinity of maize and potato starches disappears by gelatinization in the temperature range where DSC reveals endothermic transitions. Room temperature SAXS patterns are understood in terms of the scattering from stacks of alternating crystalline and amorphous layers. During gelatinization, the SAXS stack scattering and the WAXD crystallinity decreases in parallel while additional SAXS appears at very low angles, due to temporarily remaining fragmented sheets of semicrystalline blocklets, being remnants of granules in the course of gelatinization. The amount of such temporarily remaining blocklets is much lower in potato starch than in maize starch likely as a result of a more rapid and complete individual granular conversion for potato starch. Remarkably, in maize starch the blocklet scattering appears prior to crystal melting, suggesting that water sorption induces blocklet separation prior to actual gelatinization. In potato starch, such early separation is not observed, likely because blocklet connecting, long chain amylose molecules prevent the pre-gelatinization separation process. Graphical abstract: Image 1 Highlights: New SAXS interpretation scheme for non-simultaneously gelatinizing starch granules. Gelatinization temporarily leaves separated semicrystalline blocklets. Quantification of closely packed, separated and fully gelatinized blocklet fractions. Blocklets in A-type maize starch partially disconnect prior to gelatinization. Quantification of water content in amorphous layers.